REPRESENTATION OF MUTUAL TERMS AND RESEARCH SKILLS TOWARDS GRADE POINT AVERAGE: EXPLORATION STUDY - Hasan Subekti; Wachidatul Linda Yuhanna; Herawati Susilo; Ibrohim Ibrohim; Hadi Suwono (Florea: Jurnal Biologi dan Pembelajarannya)
Research activities have been studied extensively to improve the quality of learning, especially in higher education. This research aims to explore the mastery of the term of research ( TR or IR ) and research skills (RS or KR) of toward of grade point average (GPA or IPK). This research uses a quantitative approach to the object of students in natural science education program a number of 67 people who follow biotechnology courses academic year 2017/2018. Data collection with tests and aggregation of documentation. Data analysis technique is done by quantitative descriptive analysis. The decision indicates that the exact number of IR is 66.0 (easy category) and KS is 65.8 (short category). The result of correlation analysis shows ð¹ð‘ð‘œð‘¢ð‘›ð‘¡ = 6,147Ëƒ 3,140 = ð¹ð‘¡ð‘Žð‘ð‘™ð‘’ = (0,05;2;64) or in other words there a relationship of IR and KR collectively to GPA. This study concludes that there is a significant correlation between IR and KR guards in the same period as the GPA. Based on the investigation, it is expected to provide benefits as one of the considerations for the selection and determination of learning mods related to learning. It is expected to be useful as a consideration for the selection and determination of study-related modes for improvement.